Dynamic monitoring of viral gene expression reveals rapid antiviral effects of CD8 T cells recognizing the HCMV-pp65 antigen - Khan, Fawad; Müller, Thomas R.; Kasmapour, Bahram; Ynga-Durand, Mario Alberto; Eiz-Vesper, Britta; von Einem, Jens; Busch, Dirk H.; Cicin-Sain, Luka (Frontiers in Immunology, 2024)
Introduction Human Cytomegalovirus (HCMV) is a betaherpesvirus that causes severe disease in immunocompromised transplant recipients. Immunotherapy with CD8 T cells specific for HCMV antigens presented on HLA class-I molecules is explored as strategy for long-term relief to such patients, but the antiviral effectiveness of T cell preparations cannot be efficiently predicted by available methods. Methods We developed an Assay for Rapid Measurement of Antiviral T-cell Activity (ARMATA) by real-time automated fluorescent microscopy and used it to study the ability of CD8 T cells to neutralize HCMV and control its spread. As a proof of principle, we used TCR-transgenic T cells specific for the immunodominant HLA-A02-restricted tegumental phosphoprotein pp65. pp65 expression follows an early/late kinetic, but it is not clear at which stage of the virus cycle it acts as an antigen. We measured control of HCMV infection by T cells as early as 6 hours post infection (hpi). Results The timing of the antigen recognition indicated that it occurred before the late phase of the virus cycle, but also that virion-associated pp65 was not recognized during virus entry into cells. Monitoring of pp65 gene expression dynamics by reporter fluorescent genes revealed that pp65 was detectable as early as 6 hpi, and that a second and much larger bout of expression occurs in the late phase of the virus cycle by 48 hpi. Since transgenic (Tg)-pp65 specific CD8 T cells were activated even when DNA replication was blocked, our data argue that pp65 acts as an early virus gene for immunological purposes. Discussion ARMATA does not only allow same day identification of antiviral T-cell activity, but also provides a method to define the timing of antigen recognition in the context of HCMV infection.